Analisis Pengaruh Karakteristik Dewan dan Modal Intelektual terhadap Profitabilitas pada Sektor Perbankan di Bursa Efek Indonesia - Mariska Ramadana; Wisnu Yuwono; Robin Robin (Universitas Pendidikan Indonesia, 2022)
This study aims to analyze the effect of Women on Board, Director Educational Background, and Intellectual Capital (IC) on banking performance as measured by ROA and ROE in the 2016-2020 period. This study adopts the Value Added Intellectual Coefficient (VAIC) as an IC indicator, but adds a focus on the implications of individual components on company performance. The results of the study reveal that VAIC has a direct positive significant effect on ROA and ROE. The percentage of women on the board of directors was found to have a significant negative effect on ROA and ROE. The educational background (Edu) of the board of directors shows a positive and insignificant effect on ROA and ROE. The results of the analysis of the individual components of VAIC show that HCE has a significant positive effect on ROE, which means that banks prefer HCE as a financial predictor that can increase the bank's ability to generate net income for investors. Meanwhile, for ROA indicators, banks prefer CEE to be an important component to improve performance, in line with research results which show a significant positive effect. In line with technological developments, the bank is very focused and considers human resources the most to increase profitability.